Coupled Coincidence Points in Partially Ordered Cone Metric Spaces with a c-Distance - Wasfi Shatanawi; Erdal Karapınar; Hassen Aydi (Journal of Applied Mathematics)
Cho et al. (2012) proved some coupled fixed point theorems in partially ordered cone metric spaces by using the concept of a c-distance in cone metric spaces. In this paper, we prove some coincidence point theorems in partially ordered cone metric spaces by using the notion of a c-distance. Our results generalize several well-known comparable results in the literature. Also, we introduce an example to support the usability of our results.